A low frequency oscillation suppression method for grid-connected DFIG with virtual inertia. (January 2023) - Ma, Jing; Jie, Hetong; Zhou, Yi; Shao, Hongfei; Zhao, Shuqiang; Du, Yanling; Wang, Jingran; Sun, Sujuan; Huang, Yuanyan; Shen, Yaqi
Highlights: Proposing a method based on dynamic energy curvature for suppressing oscillations. Supplementary energy branches effectively improve curvature of DFIG terminal energy. Compensation branches can achieve rapid suppression within a few seconds. Improving oscillation suppression while also improving the frequency support capability. Control structure is simple and clear, and calculation time is greatly reduced. Abstract: This paper addresses the problem that grid-connected doubly-fed induction generators (DFIG) with virtual inertia control cannot simultaneously take into account both rotor angle stability and system frequency regulation. Based on the dynamic energy curvature, a method of suppressing low frequency oscillation that considers the effect of frequency regulation is proposed. First, according to the relationship between the system stability and the dynamic energy of DFIG, the energy curvature model of the system is constructed. From that a detailed expression of the energy curvature is obtained, so that current compensation terms can be inversely deduced, and compensation branches can be constructed accordingly to improve the energy curvature during low frequency oscillation. Further, with the goal of optimizing both energy curvature and frequency regulation, a branch parameter optimization scheme is established. This scheme places equal emphasis on oscillation suppression and frequency support in order to maximize the capability of DFIG in both oscillation suppression and frequency regulation. Finally, the proposed method is verified through simulation tests performed in RTDS according to the parameters of a real grid-connected wind farm. The results show that, by ensuring the steady-state frequency deviation and reducing the maximum frequency deviation, this method can effectively increase the energy curvature, quickly suppress the low frequency oscillation in various disturbance cases, and simultaneously improve the frequency support capability of DFIG.